Інноваційна діяльність авіакомпаній - Цимбалістова, О. А.; Tsymbalistova, O. A.; ORCID: http://orcid.org/0000-0001-8565-3710; Турсунов, А. Т.; Tursunov, A. T.; ORCID: http://orcid.org/0000-0002-6234-7486 (Причорноморські економічні студії. - 2019. - Вип. 38, ч. 2. - С. 10-13, 2019)
У статті розглядаються питання вибору стратегії інноваційної діяльності, формування системи інноваційного планування, організації інноваційної діяльності авіакомпанії, підтримки творчої активності персоналу авіапідприємства. Досліджено тенденції ринку авіаційних перевезень України, його ємність та динаміку. Проаналізовано напрями інноваційної діяльності українських авіакомпаній, які визначають короткостро¬кові та довгострокові конкурентні пере¬ваги товарів і послуг підприємства порів¬няно з іншими суб’єктами господарювання. Особливо це стосується діяльності авіакомпаній, оскільки ринок авіаційних послуг постійно змінюється, зростають вимоги споживачів до якості авіатранспортного сервісу, трансформуються бізнес-моделі та стратегії конкурентної боротьби авіаперевізників. Визначено особливості інноваційної діяльності авіакомпаній, структура інноваційного процесу на експлуатаційному авіапідприємстві.

The article is devoted to the research of the current state of innovation activity of airlines in Ukraine and the substantiation of structure of the construction in innovation process. The tendencies of air transportation market of Ukraine are examined. Innovative way of the development stimulates to the complex solution of the problem of the increase of the level of innovative activity of domestic companies and to the realization of innovative projects connected with the modernization of the park of aircrafts, presentation of new kinds of services to the market, their informational guidance etc. It is the logistic approach which allows to effectively administrate the combination of streams which arise in the process of innovative activity of airline companies, lets model the configuration of innovative system in main and attendant streams. The modern feature of the airline's innovation activity is the complex nature the busi¬ness changes, the presence of poorly predictable, random components the cycle of transport activity, which obliges to organize innovative activities while adhering to the rigid structure of innovation activity. The main directions of development in the air transport production in the airline companies of Ukraine are analyzed. It is determined that at present, the most relevant innovations related to aircrafts, organization and sales of Ukrainian airline companies for Ukrainian airlines. It is established that the peculiarities of the airline's innovation activity are directly or indirectly reflected in the structure of the innovation process on the operating airline. The aspects of support of creative activity of the personnel in the part concerning innovative offers and peculiarities of changes in the organizational structure of the airline during the innovations are analyzed. It came on the conclusion that the renewal of the airline's airline during the innovation activity covers the entire air transportation process and is formed at the stage of development of innovations, which requires state support at all stages of the innovation process on the operating airline.

В статье рассматриваются вопросы выбора стратегии инновационной дея-тельности, формирования системы инновационного планирования, организации инновационной деятельности авиакомпании, поддержки творческой активности персонала авиапредприятия. Исследованы тенденции рынка авиационных перевозок Украины, его емкость и динамику. Проанализированы направления инновационной деятельности украинских авиакомпаний, которые определяют краткосрочные и долгосрочные конкурентные преимуще¬ства товаров и услуг предприятия по сравнению с другими субъектами хозяйствования. Особенно это касается деятельности авиакомпаний, поскольку рынок авиационных услуг постоянно меняется, растут требования потребителей к качеству авиатранспортного сервиса, трансформируются бизнес-модели и стратегии конкурентной борьбы авиаперевозчиков. Определены особенности инновационной деятельности авиакомпаний, структура инновационного процесса на эксплуатационном авиапредприятии.
Innovative activity of aircraft
Цимбалістова О. А. Інноваційна діяльність авіакомпаній / Цимбалістова О. А., Турсунов А. Т. // Причорноморські економічні студії. - 2019. - Вип. 38, ч. 2. - С. 10-13.
Keywords: авіакомпанія; інноваційна діяльність; стратегія інновацій; планування; організація; інноваційний процес; авиакомпания; инновационная деятельность; стратегия инноваций; планирование; организация; инновационный процесс; airline; innovation; innovation strategy; planning; organization; innovation process; Економічні науки. Економічна безпека. Economics. Economic Security. Экономические науки. Экономическая безопасность; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина